PENGARUH PENGEMBANGAN KARIR, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. BANK XYZ, KANTOR PUSAT - Sulistyorini, Melinda; Pogo, Tajjudin (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2019)
Abstract This study is intended to analyze the influence of career development, work environment, and motivation on the performance of employees of PT Bank XYZ, Head Office. This type of research is a quantitative approach. The number of respondents was 82 employees. The analytical method used is multiple linear regression, and the results of this study indicate that there are positive and significant effects of each independent variable, namely career development, work environment, and motivation on employee performance. Likewise simultaneously or together - the positive and significant influence of career development, work environment, and motivation on employee performance. Actualization needs are the strongest dimension to the dimensions of work quality. It is expected that PT Bank XYZ may not ignore programs that can develop employee motivation, such as incentives or promotions.